City‐level housing trust funds: Lessons from key case studies. Issue 4 (10th December 2021) - Beard, Virginia
Abstract: The United States needs more housing. The need for the creation of new housing and rehabilitation of existing housing stock at price points that middle‐ and working‐class families can afford has created a pent‐up demand revealed in housing assessment reports across the country. Housing trust funds have been increasingly used as one tool among other efforts to meet this proven need for more affordable housing (affordable housing is understood to mean paying less than 30% of household income on housing costs, otherwise stated as the 30% of income affordability threshold). This paper explores this important tool, overviewing crucial information needed by scholars of affordable housing as well as policymakers, housing advocates, and other stakeholders to understand and act in the use of this vehicle to support affordable housing. Little research exists on understanding the way housing trust funds are constructed and used looking across specific funds. There exists an even greater gap in investigation of the efforts of housing trust funds at local levels. Thus, this paper examines housing trust funds in a comparative manner and does so using city‐level, as opposed to state or federal‐level, funds. There exist key lessons that can be learned from cities around the country that are already engaged in such work. There are three crucial aspects that define successful housing trust funds: funds must be rooted in empirical data on housing needs and feasibility, supported by a dedicated revenue stream drawing ideally from multiple sources is indispensable and management of the fund should be established in context with other efforts at providing and retaining housing at affordable prices. The combination of housing trust fund dollars with other efforts, made stable by dedicated sources of revenue and ongoing research makes them a tool that is a successful addition to work done on supplying the demand for housing at needed price points. Resumen: Estados Unidos necesita más viviendas. La necesidad de la creación de nuevas viviendas y la rehabilitación de las viviendas existentes a precios asequibles para las familias de clase media y trabajadora ha creado una demanda reprimida que se revela en los informes de evaluación de viviendas en todo el país. Los fondos fiduciarios de vivienda se han utilizado cada vez más como una herramienta entre otros esfuerzos para satisfacer esta necesidad comprobada de viviendas más asequibles. Este documento explora esta importante herramienta, con una descripción general de la información crucial que necesitan los estudiosos de la vivienda asequible, así como los formuladores de políticas, los defensores de la vivienda y otras partes interesadas para comprender y actuar en el uso de este vehículo para apoyar la vivienda asequible. Existe poca investigación sobre la comprensión de la forma en que se construyen y utilizan los fondos fiduciarios de vivienda mirando a través de fondos específicos. Existe una brecha aún mayor en la investigación de los esfuerzos de los fondos fiduciarios de vivienda a nivel local. Por lo tanto, este documento examina los fondos fiduciarios de vivienda de una manera comparativa y lo hace utilizando fondos a nivel de la ciudad, en lugar de fondos a nivel estatal o federal. Existen lecciones clave que se pueden aprender de las ciudades de todo el país que ya están comprometidas con ese trabajo. Hay tres aspectos cruciales que definen los fondos fiduciarios de vivienda exitosos: los fondos deben basarse en datos empíricos sobre las necesidades y la viabilidad de la vivienda, respaldados por un flujo de ingresos dedicado que, idealmente, de múltiples fuentes es indispensable y la administración del fondo debe establecerse en contexto con otros esfuerzos para proporcionar y retener viviendas a precios asequibles. La combinación de dólares del fondo fiduciario de vivienda con otros esfuerzos, estabilizados por fuentes de ingresos dedicadas y la investigación en curso, los convierte en una herramienta que es una adición exitosa al trabajo realizado para suplir la demanda de vivienda a los puntos de precio necesarios. 摘要: 美国需要更多住房。新住房建造和现有存量住房修复的价格位于中产和工薪家庭可负担范围内—这一迫切愿望已在全国住房评估报告中显示了积压已久的需求。住房信托基金已越来越多地被用作一项工具，和其他措施一起实现这一经证实的、对更多的可负担住房的需求。本文探究了该重要工具，概述了研究可负担住房的学者和决策者、住房倡导者以及其他利益攸关方所需的关键信息，以期理解该工具并采取行动支持可负担住房。鲜有研究聚焦于分析住房信托基金的建构方式和被用作具体基金的方式。更少的研究聚焦于地方层面的住房信托基金举措。因此，本文通过比较视角分析城市级住房信托基金（相对于州级或联邦基金）。已参与这类基金举措的美国城市能提供关键经验。成功的住房信托基金依赖三个关键方面：基金必须基于有关住房需求和可行性的实证数据、 使用专用收入流（最好源自多个来源）、基金管理应在其他提供和维持可负担价格住房的举措情境下进行。住房信托基金和其他举措的结合，通过专用收入来源和研究加以稳定，让其成为一种工具，作为"为满足可负担住房要求所作的努力"的一种补充。